Linguo-Cognitive Opportunities of Mass Media in Manipulating Public Consciousness - Zhumagulova В.; Karimova Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
The article describes the possibilities of the media in influencing the public consciousness. The language manipulation is considered as the main manifestation of the latent influence on the consciousness. The language manipulation is considered as the main manifestation of the hidden influence on the consciousness. Ideas, images, associations, stereotypes that can completely, and imperceptibly to the object of influence, change its attitude to the world or the picture of the world of the whole society are introduced into the consciousness of people. Among the linguo-cognitive methods of the people consciousness manipulating deserves special attention: the repetition of the same phrases; affirmation and simplification; eufemization of the media language, parceling. The results of a survey conducted among users of social networks, lead to the conclusion that some users recognize the constant presence in a social network is a waste of time. In addition to wasting time, there is a decrease in human intellectual abilities. It is necessary to find a reasonable balance between virtual and real communication in order to keep mental health